2018
DOI: 10.18410/jebmh/2018/6
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Clinical Study of Haematological Disorders in Chronic Liver Disease

Abstract: BACKGROUNDLiver plays a major role in maintaining the haematological parameters in normal and maintain the haemostasis. Liver is the storage site for iron, B12 and folic acid, which are necessary for the normal haematopoiesis. Liver also secretes the clotting factors and the inhibitors and keep the haemostasis in equilibrium. Hepatocellular failure, portal hypertension and jaundice may affect the blood picture. Chronic liver disease is usually accompanied by hypersplenism. Diminished erythrocyte survival is fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…The overall average international ratio (INR) was 1.92 [ 12 ]. Jha et al [ 14 ] and Raja et al [ 15 ] found haematological derangements, specifically leukocytosis, in CLD patients more prevalent than leucopenia and TCP; with the total number of white blood cells ranging anywhere from 1050/mm3 to 16,100/mm3 [ 15 ]. Jha et al also observed increased prothrombin time and activated partial thromboplastin time (APTT) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall average international ratio (INR) was 1.92 [ 12 ]. Jha et al [ 14 ] and Raja et al [ 15 ] found haematological derangements, specifically leukocytosis, in CLD patients more prevalent than leucopenia and TCP; with the total number of white blood cells ranging anywhere from 1050/mm3 to 16,100/mm3 [ 15 ]. Jha et al also observed increased prothrombin time and activated partial thromboplastin time (APTT) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%